Development of a sakinah family module for the majlis ta’lim congregation - Fatimah, Nabila Nurul; Indra, Hasbi (Tawazun: Jurnal Pendidikan Islam, 2026)
The family is the cornerstone of building a harmonious and morally upright society; however, in the modern era, many families face challenges such as domestic conflicts, poor communication, and a lack of understanding of Islamic values. This study aims to develop the Sakinah Family Module as an educational tool for majlis ta’lim congregations that is practical and contextually relevant. The method used is Research and Development (R&D) employing the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through needs assessments, expert validation, and user testing. The results of the study indicate that all respondents (100%) expressed a need for a Sakinah family guidance module. Expert validation showed a “highly suitable” rating, with scores of 92.9% for subject matter experts, 79.2% for language experts, and 92.9% for design experts. During the implementation phase, 80% of users rated the module as very good, and all respondents stated that the module helped them understand the concept of the Islamic family. Thus, the developed module has proven to be feasible, effective, and relevant as instructional material and a practical guide for fostering harmonious families within the majlis ta’lim setting. Abstrak Keluarga merupakan fondasi utama dalam membangun masyarakat yang harmonis dan berakhlak, namun pada era modern banyak keluarga menghadapi permasalahan seperti konflik rumah tangga, lemahnya komunikasi, dan kurangnya pemahaman nilai-nilai Islam. Penelitian ini bertujuan untuk mengembangkan Modul Keluarga Sakinah sebagai media edukatif bagi jama’ah majlis ta’lim yang aplikatif dan kontekstual. Metode yang digunakan adalah penelitian dan pengembangan (Research and Development) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Data dikumpulkan melalui angket kebutuhan, validasi ahli, dan uji coba pengguna. Hasil penelitian menunjukkan bahwa seluruh responden (100%) menyatakan kebutuhan terhadap modul pembinaan keluarga sakinah. Validasi ahli menunjukkan kategori sangat layak dengan skor ahli materi 92,9%, ahli bahasa 79,2%, dan ahli desain 92,9%. Pada tahap implementasi, sebanyak 80% pengguna menilai modul sangat baik dan seluruh responden menyatakan modul membantu dalam memahami konsep keluarga Islami. Dengan demikian, modul yang dikembangkan terbukti layak, efektif, dan relevan sebagai bahan ajar serta panduan praktis dalam pembinaan keluarga sakinah di lingkungan majlis ta’lim.